Creativity and innovation four steps to improved thinking - Hinkle, Dale. (CareerTrack Publications, 1995)
A business training program to teach creativity and innovation skills. Explains the importance of generating new ideas in today's work environment. Volume I - You'll learn how to put yourself in a creative mode any time, any place. You'll gains mental exercises that help you "think divergently". Discovers the best ways to capitalize on your "moments of inspiration". You'll learns how to maintain your momentum and get yourself going again when the well runs dry. Volume II - Teach you to break down the creative barriers that exist where you work - and establish new "norms" that wake up your creativity.